Gunshot wound to neck base - E. Bergalli, Luis; C. Castiglioni, Juan (Cirugía del Uruguay, 1971)
Traumatic injuries from a gunshot wound or stab wound to the neck, pose a serious problem in surgery of urgency. This is due to the multiple structures of vital importance that may be involved and, on the other hand, to the technical difficulties of the surgical approach to that region.